KONSTRUKSI POSTMODERN DALAM NOVEL LARUNG - Pujiharto, Pujiharto (LITERA, 2005)
This research study intends to reveal the extent to which Larung (2001), as a recent Indonesian novel, shows postmodern features, especially in its construction, concerning the worlds under erasure and the Chinese box worlds. The theory adopted in the study is that of postmodern fiction by Brian McHale. The method employed is semiotics by Hurshovsky. The theory and method are based on the assumption that postmodern fiction is ontological in nature. This is different from modern fiction, which is epistemological in nature. According to McHale, the ontological nature comprises zones, construction, words, and groundings. This study investigates, in particular, the construction in Larung. The research findings show that in Larung there are features classified by McHale into construction, covering the worlds under erasure and the Chinese box worlds. In the former, Larung explores the features proposed by McHale, namely something always happening, something always existing, excluded middles, forking paths, and a sense of a (non) ending. In the latter Larung also explores features proposed by McHale, namely moving toward infinite regression, trompe-l’oell, strange loops, characters in search of an author, abysmal fictions, and something real. However, in terms of moving toward infinite regression Larung shows opposite features; it does not narrate things backward continuously, but it moves backward and forward to the present. Therefore, Larung can be classified as novel with a postmodern construction.